Strategi Pemasaran Digital Meningkatkan UMKM Kampung Kue Rungkut Surabaya - firda Aulia; Dwi Prasetyo; Nurtyasih Wibawanti Ratna Amina (Prapanca : Jurnal Abdimas, 2022)
Micro, Small and Medium Enterprises or MSMEs are currently in great demand by the public, one of which is the culinary sector. Such as MSMEs in Kampung Kue Rungkut Surabaya, where almost the entire population is MSME business actors. This community has been established since 2001 by Choirul Mahpuduah. Having 60 trading units is able to attract more than 100 customers per day. But unfortunately, this MSME business still has shortcomings, namely promotions in online sales to product photos that are less attractive. So our team, solved the problems that exist in Kampung Kue Rungkut, in the form of socializing content writing about product marketing to be promoted in online sales, practice photos and videos of products using simple supporting elements in order to attract more customers. Therefore, this research is intended to increase the promotion of culinary products in the Rungkut village cake, Surabaya. The type of research based on the form and method of implementation in this research is a field survey with data collection techniques, including observations and interviews with several entrepreneurs and community founders there. The results of this research are socialization and increase the experience of photo and video practice to the residents of the UMKM business in the kue rungkut village.